PERBANDINGAN SIFAT FISIKO-KIMIA 5 JENIS JERNANG - Totok K. Waluyo (BRIN Publishing, 2013)
Dragon's blood is a resin secreted from the fruit of dragon's blood rattan. The resin originated from Indonesia and known in the International market is indigenous from the so-called Daemonorops draco Blume, rattan species. Species exploration in the Sarolangun regency (Jambi province) bad found 5 rattan species that are able to produce dragon's blood. Those five species are jernang burung (Daemonorops didymophylla Bec.); jernang umbut (Daemonorops melanochactes Blume.), jernang rumbai (Daemonorops draco Blume.); jernang kalamuai (Daemonorops longipes Mart.), and jernang kepala puyub (Daemonorops sp.). Physicochemical properties of dragon's blood were done based on Indonesian National Standard (SNI 1671:2010), and identification of its compounds proceeded using the gas chromatography-mass spectrophotometer. The lowest yields of dragon's blood was from D. didymophylla (1.20%), while those from other rattan species were quite bigb (11-12%). Moisture content of five rattan species ranged about 3-5%, impurities 4-6%, ash content 0-2%, and melting point 85-105°C. Dracobordin compound that serve as bio-indicator for dragon's blond is presence in all those five species. Further exploration need to be done to obtain rattan species with high potential dragon's blood resin productivity.